A corpus-based quantitative analysis of twelve centuries of preterite and past participle morphology in Dutch. (July 2020) - De Smet, Isabeau; Van de Velde, Freek
Abstract: Germanic preterite morphology has been the subject of a bewildering number of studies, looking especially at the competition between the so-called strong inflection (operating with ablaut), and the so-called weak inflection (operating with suffixation). In this study over 250, 000 observations from twelve centuries of Dutch were analyzed in a generalized linear mixed-effect model gauging the effects of a multitude of language-internal factors, ranging from various frequency measures to various form-related factors and how they interact with each other. This study confirms the well-known effects of token and type frequency, finding that formal similarities can be both a driving and conservative force in language change and demonstrates that not all members (i.e., preterites and past participles) of a verb paradigm change at the same time, which is both an effect of their frequency and their formal coherence within the paradigm.